Sulla's Tabularium - Irwin, Sean (University of Waterloo, 2010)
This thesis examines the Tabularium in Rome. Very little is written about this building, despite its imposing size and commanding location at the juncture of the Forum Romanum and the two crests of the Capitoline hill. It remains a cipher, unconsidered and unexplained. This thesis provides an explanation for the construction of the Tabularium consonant with the building’s composition and siting, the character of the man who commissioned it, and the political climate at the time of its construction — reconciling the Tabularium’s location and design with each of these factors. Previous analyses of the Tabularium dwelt on its topographic properties as a monumental backdrop for the Forum to the exclusion of all else. This thesis proposes the Tabularium was created by the dictator Lucius Cornelius Sulla as a military installation forging an architectural nexus between political and religious authority in Rome. The Tabularium was the first instance of military architecture behind the mask of a civic program — a prototype for Julius and Augustus Caesar’s monumental interventions in the Forum valley.
Keywords: Rome; architecture; Architecture